Optimization of glass furnace heat recovery exchanger parameters - Fialko, N.; Stepanova, A.; Navrodska, R.; Meranova, N.; Shevchuk, S. (Energy and Automation, 2025)
The research results on the efficiency and optimization of glass furnace heat recovery exchangers parameters using complex methods, including exergy analysis methods and optimization algorithms used in statistical experimental design theory are presented. Two types of heat recovery exchangers using the heat from exhaust gases of glass furnaces were investigated. This is an air-heating heat recovery exchanger (end recuperator) designed to preheat cold air before it enters the furnace regenerator, and a water-heating heat recovery exchanger with a staggered and corridor arrangement of pipes in a bundle, which is used in schemes for heating water in heating systems. To optimize the heat exchange surface parameters of heat recovery exchangers, a complex methodology has been developed based on an exergy approach and the canonical transformation method used in statistical experimental design theory. Within the framework of the exergy approach, exergy criteria are used that can serve to evaluate the exergy efficiency of heat recovery exchangers and as optimization objective functions (response functions) when solving optimization problems. The canonical transformation method is used as the optimization algorithm, which allows obtaining a graphical interpretation of the optimum region for the response function in the form of a series of contour curves on a plane. Functional dependencies of the efficiency evaluating criteria for air-heating and water-heating heat recovery exchangers on their main parameters in canonical form have been obtained. Graphs of specified dependencies and graphical interpretations of the optimum regions for response functions are presented in the form of a series of contour curves on a plane. A detailed study of response surfaces in the response function minimum region was conducted, and the optimal regions of geometric parameters for the heat exchange surface of air-heating and water-heating heat recovery exchanges were determined. When determining the intervals for changing parameters based on the optimal parameters exact values, the technological requirements for the heat exchange surface of heat recovery exchangers were also taken into account. The research conducted will serve to develop increased efficiency heat recovery systems.